Reassessment of Copper Mineral Occurrence Through Electrical Tomography and Pseudo 3D Modeling in Camaquã Sedimentary Basin, Southern Brazil - Moreira, César Augusto [UNESP]; Paes, Renata Augusta Sampaio [UNESP]; Ilha, Lenon Melo; da Cruz Bittencourt, Jorge (Springer Nature, 2019)
The reassessment of mineral occurrences is a common and economically rational technical procedure, because it involves studies directed to targets defined in previous studies in mineral exploration. The targets definition can be based on indications of mineralization on the surface or in the contrast of measurable physical properties using geophysics and intrinsic to certain types of deposits. This paper discusses the results by the combination of the use of geophysical methods, DC resistivity and induced polarization on detailed study of a copper mineral occurrence, from the adaptation of techniques of modeling of mineral deposits in mining. The indications of mineralization in the area consist of malachite, quartz and barite in veins, recognized in volcanic tufts structurally embedded in andesites and metaconglomerates. Nine parallel lines of electrical tomography in Schlumberger arrangement were performed, which resulted in 2-D inversion models, interpolated in models of blocks, maps and pseudo 3-D isosurface models in a mineral deposits modeling program. The results allowed the recognition of areas with high chargeability (2.5 mV/V) and high resistivity (800 Ω m), relating to areas with disseminated sulphide ores and silicification, according to recognized evidence around the area distribution in regional recognition. This is where the pseudo 3-D products enabled an estimate morphology of the deposit and clearly defined targets for sampling by drilling and quantification of results. The results allow the recommendation of this procedure in mineral exploration activities, supported by the quickness and possible global reduction of project costs, with real increase in the chances of incorporation of new deposits. This Reduces the costs for research development and minimizes the environmental impacts associated with mining as well as the application of these methods for environmental diagnosis.
Keywords: electrical resistivity tomography; geophysics; Mineral exploration; pseudo 3D modeling; sulfides